Pengaruh Islamic Banking Digital Transformation Terhadap Kepuasan dan Retensi Nasabah Melalui Customer Experience Sebagai Variabel Intervening: Migrasi BSI Mobile Ke BYOND By BSI (Penelitian di Sumatera Selatan) - Khairunisa, Khairunisa; Panorama, Maya; Cahaya Azwari, Peny; Noval Karom, Muhamad (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the effect of Islamic Banking Digital Transformation on customer satisfaction and customer retention through customer experience as an intervening variable in the migration from BSI Mobile to BYOND by BSI in South Sumatra. Digital transformation in the Islamic banking industry has become an important strategy in improving the quality of digital services, particularly in creating positive customer experiences, increasing customer satisfaction, and maintaining customer loyalty in the digital era. This study employed a quantitative approach using a survey method. The data were collected through questionnaires distributed to customers using the BYOND by BSI application in South Sumatra. The data analysis technique used in this study was Structural Equation Modeling–Partial Least Square (SEM-PLS) with the SmartPLS application. This study examined both direct and indirect effects among the variables of Islamic banking digital transformation, customer experience, customer satisfaction, and customer retention. The results of the study indicate that Islamic banking digital transformation has a positive and significant effect on customer experience, customer satisfaction, and customer retention. In addition, customer experience also has a positive and significant effect on customer satisfaction and customer retention. Furthermore, customer satisfaction is proven to have a positive and significant effect on customer retention. The findings also reveal that customer experience partially mediates the effect of Islamic banking digital transformation on customer satisfaction and customer retention. Overall, this study demonstrates that the success of digital transformation in Islamic banking is not only determined by technological sophistication, but also by the bank’s ability to create positive customer experiences that can enhance customer satisfaction and sustain customer loyalty. This study is expected to provide theoretical and practical contributions to the development of digital transformation in the Islamic banking industry in Indonesia.